Detection of leptospira species by polymerase chain reaction (PCR) in urine of cattle - Çetinkaya, B; Ertas, HB; Öngör, H; Muz, A (Scientific Technical Research Council Turkey, 2000)
This study was carried out to investigate the prevalance of leptospirosis in the urine of cattle slaughtered in three major abattoirs in the east of Turkey. A polymerase chain reaction (PCR) based on a pair of genus-specific primers was used to detect leptospiral DNA in the urine samples of 473 cattle, 284 of which were from Eiazig, 112 from Malatya and 77 from Diyarbakir. The detection limit of the method was determined to be approximately five bacteria per mi of urine. Tn the examination of urine samples, 4.02% (19/473) (95% confidence intervals [Cl] 2.4-6.2) were found to be positive by PCR. The prevalance of disease was determined to be 3.6% (9/250) (95% Cl 1.7-6.7) in males and 4.5% (10/223) (95% Cl 2.2-8.1) in females, but the difference according to sex was not statistically significant (P=0.79). When the prevalance was calculated in different abattoirs, the highest proportion was obtained in Elazig with 4.9% (14/284) (95% CI 2.7-8.1), and the lowest in Malatya with 1.8% (2/112) (95% CI 0.2-6.3). However, die difference between the abattoirs was not significant (P=0.35).
Keywords: leptospira; cattle; urine; prevalence; PCR